The effect of portfolio assessment on Iranian pre-intermediate EFL learners’ autonomy - Hassan Soodmand Afshar (Teaching English Language, 2012)
The present study set out to address the issue as to whether the implementation of portfolio assessment would give rise to Iranian pre-intermediate EFL learners’ autonomy. Participants comprised 60 pre-intermediate female learners within the age range of 16 to 28 studying English in a private language institute, a Cambridge Open Centre (IR056). They were randomly divided into two groups each consisting of 30 participants. An independent sample t-test confirmed their homogeneity in terms of language proficiency at the outset of the study. Moreover, they were homogenized in terms of autonomy through employing a validated questionnaire. The portfolio assessment was integrated into the experimental group while traditional assessment was assigned to the control group. The study adopted a mixed-method approach for the purposes of data collection and analysis. Data were collected by means of a questionnaire, a semi-structured interview, and participants’ portfolios. Quantitative data were analyzed using independent samples t-test. Qualitative data were analyzed inductively through content analysis. The recurring themes emerging from the interview and participants’ portfolios were compared with the findings of the questionnaire. The results of both quantitative and qualitative data analyses revealed that portfolio assessment significantly enhanced learner autonomy in the experimental group, and offered them an opportunity to reflect upon their learning process, growth, and progress overtime. Drawing upon the findings, some pedagogical implications are presented and finally, some avenues for future research are highlighted.